ANALISIS YURIDIS TERHADAP PRAKTIK RESTRUKTURISASI KREDIT PASCA PANDEMI - Bambang Fitrianto; Dewi Fortuna Manulang; Andhika Tri Dharmawan; Luthfi Alghifari Batubara; Sinta Grace Ika Sianturi; Suntya Indah Lestari (Judge : Jurnal Hukum, 2025)
The COVID-19 pandemic has caused a decline in economic activity and increased the risk of problematic credit, thereby endangering the stability of the financial sector, especially banking. To maintain the availability of cash in banks and help affected debtors, the government through the Financial Services Authority (OJK) is implementing a credit restructuring policy. This research uses a normative juridical approach and literature study to evaluate the legal basis, implementation, and impact of credit restructuring policies after the pandemic. The research results show that the restructuring policy has a strong legal basis. This is indicated by POJK No. 11/POJK.03/2020 and its derivative regulations, the Banking Law, and civil law principles (Article 1338 of the Civil Code). Although restructuring increases the stability of the financial system and benefits debtors economically, it also raises problems such as the risk of moral hazard and debtors' dependence on payment slack. Therefore, to ensure that this policy is successful in the long term, consistent monitoring and application of the precautionary principle is essential.